Aktualisasi Nilai-nilai Pancasila sebagai Dasar Falsafah Negara dan Implementasinya Dalam Pembangunan Karater Bangsa - Sutan Zabda (Jurnal Pendidikan Ilmu Sosial, 2016)
The problems discussed in this paper were; 1) why the Pancasila (the five Indonesian National Principles) values had not been fully understood and acted in the Indonesian, 2) how Pancasila Values could be revitalised so that it could be characteristically internalised in the daily society activities.Based on the deep review from some theories, the conclusions were: 1) the tentative manners were the main problems of unimplemented Pancasila values in the most Indonesian. 2) The Pancasila values must be revitalised trough seriously dissemination process with the appropriate strategies and scientifically instead of doctrine. Every effort of Pancasila values internalisations must use persuasion approach.